2003
DOI: 10.1046/j.1570-7458.2003.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S‐transferase detoxification as a potential pyrethroid resistance mechanism in the maize weevil, Sitophilus zeamais

Abstract: Insecticide resistance patterns among 16 Brazilian populations of the maize weevil, Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae), were recognized by surveying resistance to three organophosphates (chlorpyrifos‐methyl, malathion, and pirimiphos‐methyl) and three pyrethroids (cypermethrin, deltamethrin, and permethrin). Two population clusters were obtained: one with three populations (Bragança Paulista, Cristalina, and Nova Andradina) showing low frequency of cypermethrin resistance (13–36%) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 29 publications
1
64
0
Order By: Relevance
“…The JA and JF strains exhibit resistance to cypermethrin, but the resistance levels were only low and moderate respectively, in contrast with the original strains from which they were derived (Guedes et al ., , ; Fragoso et al ., ; Ribeiro et al ., ; Corrêa et al ., ). Arbitrary divergence from the original (parental) colonies certainly occurred during the establishment and maintenance of the derived colonies used in our study, which has already been demonstrated to occur (Fricke & Arnqvist, ).…”
Section: Discussionmentioning
confidence: 97%
“…The JA and JF strains exhibit resistance to cypermethrin, but the resistance levels were only low and moderate respectively, in contrast with the original strains from which they were derived (Guedes et al ., , ; Fragoso et al ., ; Ribeiro et al ., ; Corrêa et al ., ). Arbitrary divergence from the original (parental) colonies certainly occurred during the establishment and maintenance of the derived colonies used in our study, which has already been demonstrated to occur (Fricke & Arnqvist, ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the frequent unsuitable storage management added to poor fumigant application techniques has probably enhanced the selection pressure for resistance , Lorini et al 2007, Pimentel et al 2007. Another factor that can influence the evolution of phosphine resistance is the movement of insects due to the commodity trade (Benhalima et al 2004, Fragoso et al 2003b.…”
Section: Discussionmentioning
confidence: 99%
“…The maize weevil is no exception and high levels of insecticide resistance, particularly pyrethroid resistance, have been reported (Guedes et al. 1994, 1995; Perez‐Mendoza 1999; Fragoso et al. 2003; Ribeiro et al.…”
Section: Introductionmentioning
confidence: 99%